Inflammatory Bowel Disease in Maldives; A Single Center Clinical Experience - Khadka, Mohan (Birat Journal of Health Sciences, 2021)
Introduction: Inflammatory bowel disease (IBD), once considered disease of west is also increasingly diagnosed in Asia in recent years. As there are already studies about IBD in Southeast Asia like India, Srilanka, it would be more informative to study the disease in Maldives as being closer to India and Srilanka. This is probably the first study about the disease from Maldives conducted in a single tertiary hospital center. The objectives of the study were to determine the prevalence, clinical characteristics and treatment of IBD in Maldives. Methodology: A preliminary hospital-based retrospective observational study was performed in ADK multispecialty hospital, a referral tertiary center located in the capital city of Maldives. Patients visiting gastroenterology OPD, who were diagnosed as IBD either Crohn’s disease (CD) or Ulcerative colitis (UC) on basis of internationally established standard practice, were recruited in the study after informed oral consents for the duration of three years from January, 2017 to December, 2020. We collected clinical data including gender, age at diagnosis, symptomatology, severity, smoking habits, family history, disease phenotype, and behavior at diagnosis from each involved patients as per clinical proforma prepared for UC and Crohn’s disease in separate forms. Result: Total 41 patients of IBD with 15 CD and 26 UC were recruited during study period. The prevalence of IBD in the country was estimated to be at least 20 per 100000 persons. Ileocolonic phenotype in CD and Extended colitis in UC were more common. Clinically, majority IBD patients presented with moderate to severe form. Biologic agents were frequently used in IBD. Conclusion: The prevalence of IBD in Maldives is also more or less similar to other Asian countries where as some aspects of clinical characteristics are similar to Western countries. There needs to be nationwide epidemiological study or multi center hospital based prospective or at least cross sectional study for detail and optimal information about various aspects of IBD.